RELATIONSHIP OF INSECURITIES AND PERCEPTION OF SELF WITH MENTAL WELLBEING - Ambrien Ahmed (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2021)
The purpose of the present study was to study the relationship of insecurities and perception of self with the mental wellbeing in early adults. For this study, a sample of 73 participants were taken through a random sampling method from the early adulthood age group of 20-30 years. It has been suggested that when insecurities emerge due to ecological, situational, or internal edifices, the human propensity to see oneself changes either in a positive manner or a pessimistic way, which, in one or the other case, affects the emotional well-being of the individual. The results of study showed positive correlationof perception of self with mental wellbeing whereas negative correlation of insecurities with mental wellbeing. Keywords: Mental Wellbeing, Self-Perception, Psychological Insecurity